The Challenge Of Justice Soluble In Intelligence - BADI BOUKEMIDJA, Nadjiba (University of Eloued جامعة الوادي, 2020)
The progression of artificial intelligence resulted into an amplification relating to application, which arrived to the field of justice. Thus, we notice that the man of law is replaced by the machine. For this purpose, justice is expected to anticipate the solutions relating to exposed problems, it will then take the form of predictive justice, which makes the judgments and awards pseudonymized, and based on judicial Big data, which is not limited to judicial information, usually withdrawn from texts. But it is also concerned by the way to make rise juridical problem, as this method shall be intelligent, as it comes from algorithmic trial.
مجلد11، عدد3
Keywords: artificial intelligence ; big data ; justice ; algorithmic ; predictive